VD_FINDINFO Jug / 2024 / 97 vom 25. Juli 2023 - VD Tribunal cantonal (2023)
CONSTATATION DES FAITS, PRÉSOMPTION D'INNOCENCE, PROTECTION DE LA PERSONNALITÉ, DROIT D'ÊTRE ENTENDU, DÉPENS | 49 al. 1 CO, 10 CPP (CH), 3 al. 2 let. c CPP (CH), 398 al. 3 let. b CPP (CH), 433 al. 1 CPP(CH)